Enhancing Fraud Detection: Roles of Skepticism, Audit Technology, and Industry Specialization in Indonesia - Rusli, Arrum Azzahra; Yusnaini, Yusnaini; Sukanto, Sukanto (International Ecsis Association, 2025)
Fraud remains a persistent threat to financial reporting, particularly in developing countries like Indonesia where corruption is deeply entrenched. Despite advancements in auditing standards, limitations in fraud detection continue to undermine audit quality and public trust. This study aims to investigate the impact of professional skepticism, auditor ethics, and audit technology on fraud detection, with auditor industry specialization as a moderating variable. Using a quantitative approach, data were collected via questionnaires from 233 public accountants across 88 Indonesian public accounting firms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that professional skepticism and audit technology significantly enhance fraud detection, while auditor ethics does not show a direct significant effect. Industry specialization significantly moderates the relationship between professional skepticism and fraud detection, as well as between auditor ethics and fraud detection. However, it does not moderate the effect of audit technology on fraud detection. These results suggest that skepticism and technology are critical competencies in fraud detection, but their effectiveness is further amplified when coupled with contextual industry expertise. Conversely, ethical awareness alone is insufficient unless supported by domain-specific knowledge. The study underscores the importance of enhancing professional training and developing sector-specific audit practices to strengthen fraud detection capabilities in Indonesia.